INTEGRASI PEMIKIRAN ISLAM DAN PERADABAN MELAYU: STUDI EKSPLORATIF HISTORIS TERHADAP PERKEMBANGAN PERADABAN MELAYU ISLAM DI NUSANTARA - Mugiyono Mugiyono (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Integration of Islamic thought and civilization Malays make acculturation and assimilation between them to give birth to new style of Islamic Malay civilization which has its own distinct characteristics with Islamic civilization elsewhere. Dynamics of Islamic thought in the Malay lands have created the character of Malay Islamic civilization. Islam became the unifying factor of various ethnic Malays. 'supra-identity' across geographical boundaries, ethnic sentiments, customs and traditions of the local Malays. Malay is as'lingua franca' by Muslim scholars, clerics, and merchants. He has an important role in the formation of the intellectual tradition of Islam in the Malay World archipelago that produce scientific work in various fields. These works developed over time, so it has great influence in the formation of social-intellectual tradition of Islam in the frame of Islamic civilization in the Malay Archipelago. The influence of Islam in the Malay civilization not only in the religious order, but more extensive and comprehensive, of which include; science, politics, culture, customs, art, literature, language, laws and other Malays.